Identification, Pathogenesis and Virulence Test of Fungus Causes Postharvest Disease of Gedong Gincu Mango from Pal Market, Cimanggis, Depok - Arti, Inti Mulyo; Asnur, Paranita; Kurniasih, Ratih; Ramdan, Evan Purnama (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
Mango is a climacteric fruit that can increase in maturity after harvest. As a result, mangoes will rot more easily because they are infected with pathogens such as fungi. The objectives of the study were to identify, examine the pathogenicity, and virulence of the fungus that causes postharvest disease in mangoes. Sampling of mangoes was carried out at the Pal market, Cimanggis, Depok by selecting fruits that were indicated to be infected with post-harvest diseases. Symptoms that appear are then described visually. Isolation of the fungus was carried out from the part of the mango fruit on Potato Dextrose Agar (PDA) media, then it was identified morphologically both macroscopically and microscopically. The virulence test was carried out by inoculating the fungus at 4 inoculation points of mango fruit. The results showed that the symptoms that appeared were symptoms of anthracnose in the form of blackish brown, sunken, and widespread spots on the mango skin. The results of morphological identification showed that the associated fungus was Colletotrichum gloeosporiodes which was characterized by white fungal colonies and fast growth, while the condia were cylindrical in shape with rounded ends. Confirmation results with Koch's postulates showed that postharvest anthracnose in mangoes was caused by C. gloeosporiodes. Meanwhile, virulence testing showed that C. gloeosporiodes had moderate to high virulence levels with symptomatic lesions ranging from 2,50 to 5,85 cm.